Runoff forecasting using fuzzy support vector regression - Wiriyarattanakul S. (2014)
The Runoff forecasting is an important factor in river basin management. In this paper, we use fuzzy support vector machine regression (FSVMR) to predict the Runoff of Yom River at Sukhothai province, Thailand. The results show that the FSVMR is a suitable method in forecasting Runoff.